Knowledge Accessibility and the Marketing Mix Service of Thai Traditional and Alternative Medicine that Affects Service Quality A Case Governmental Hospitals Nonthaburi Province - Jansathian, Mintra; Potongsangarun, Rujipas (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This research has purposes 1) to study the influence of social factors which has affected the decision to purchase vitamin C beverages. 2) To study the influence of lifestyle factors through the attitude factors which has affected the decision to purchase vitamin C beverages. 3) To study the influence of attitude factors which has affected the decision to purchase vitamin C beverages. 4) To study the influence of brand equity factors which has affected the decision to purchase vitamin C beverages. 5) To study the influence of 4Es marketing strategy factors which has affected the decision to purchase vitamin C beverages. The research instrument consisted of validity questionnaires consumed to collect the data. The sample group of the studying is 400 consumers in the age range 15 years and over who have ever drunk vitamin C beverages. The data was analyzed by Descriptive Statistics such as percentage, mean, standard deviation, and Inferential Statistics such as elemental analysis, Structural Equation Model analysis (SEM). The results show that the 4Es Marketing Strategy and the Attitude factor have directly influenced the consumers' decision to purchase vitamin C beverages. And the Lifestyle factor has an indirect influence through the Attitude factor, while the social factor and Brand Equity are non-influence the decision to purchase vitamin C beverages.